Effect of disturbance on fine root biomass in the Tropical moist forest of eastern Nepal - Gautam, Tilak Prasad; Mandal, Tej Narayan (Nepalese Journal of Biosciences, 2013)
Fine root biomass (<5 mm diameter) was estimated in 0-15 cm and 15- 30 cm soil depths of disturbed and undisturbed stands of tropical moist forest in eastern Nepal. The value of root mass was higher (4.28 t ha-1) in the undisturbed stand than the disturbed stand (2.04 t ha-1). The biomass of smaller fine roots (<2 mm diameter) was 1.51 and 3.2 t ha-1 in the disturbed and undisturbed stands respectively. Most of the fine roots were present in the surface soil layer (0-15 cm), in both the disturbed and undisturbed stands (67% in the disturbed and 64% in the undisturbed). The nitrogen stock in the fine roots was more (38.61 kg ha-1) in undisturbed stand than the disturbed stand (16.93 kg ha-1). More nitrogen was confined in the fine roots of <2 mm diameter in both undisturbed (28.8 kg ha-1) and disturbed (13.59 kg ha-1) stands. DOI: http://dx.doi.org/10.3126/njbs.v2i0.7484 Nepalese Journal of Biosciences 2 : 10-16 (2012)